(untitled) (مجلة جامعة دمشق للعلوم الاقتصادية و السياسية, 2025)
The role of the banks in financing small-sized enterprises has become a focus of attention for decision-makers around the world, given their economic and social importance to the economies of both developed and developing countries. However, they face several problems and the most important of which is financing. Financing the subject of this study where the problem of study lies in the limited and non-diversified sources of financing small businesses. The study is based one main hypothesis, which states that, “there is no significant relationship between financing by debt and the profitability of small enterprises”. The importance of this study stems from extending the base of investment in banks as small businesses represent a new and huge market for financing agencies.